Analysis of the ecological agriculture sector in the Republic of Moldova - Galina Ignat; Anatolie Ignat (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 13th Edition, 2022)
The general purpose of this article is the analysis of the organic agriculture sector in the Republic of Moldova, determining the place of this sector in the national economy, as well as highlighting the advantages and disadvantages of this sector. In the process of developing this article, such research methods as statistical analysis of existing data, comparative analysis, synthesis of existing information, deduction method, and SWOT analysis were applied. Following the use of research methods, quantitative parameters were established that define the place of organic agriculture in the economy of the Republic of Moldova, the importance of organic agriculture in particular in the current conditions of agricultural development that involve such factors as: climate change, environmental pollution, inefficient use and abuse of natural resources, etc. The industrial model of agricultural intensification widely used in the last decades did not ensure a sustainable development of the agricultural sector. As a result, organic agriculture is gaining more and more importance and demonstrates dynamic development trends. The practice of organic farming is dictated by market demand, with consumers increasingly demanding healthy, organic, naturally grown agricultural and food products.
Keywords: Q10; Q13; Q15; 330; ecological agriculture; ecological agricultural product; economic analysis